2015
DOI: 10.1007/s11999-015-4338-2
|View full text |Cite
|
Sign up to set email alerts
|

Tantalum Cones Provide Durable Mid-term Fixation in Revision TKA

Abstract: Background Multiple studies have reported favorable short-term outcomes using tantalum cones to reconstruct massive bone defects during revision TKA. However, longer-term followup is needed to determine the durability of these reconstructions. Questions/purposes We wished to determine the midterm (1) reoperation rates for septic and aseptic causes, (2) radiologic findings of osseointegration, and (3) clinical outcomes based on the Knee Society score in patients who underwent revision knee arthroplasty with tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 45 publications
1
60
0
5
Order By: Relevance
“…In 2015 three papers with considerable population and midterm follow-up were published. De Martino et al [68] described their results with 26 (both femoral and tibial) cones at 72 months of follow-up. No evidence of loosening of the cones was detected, and the authors stated that tantalum cones for reconstruction of massive bone defects provided secure fixation and outcomes at average follow-up of 6 years.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…In 2015 three papers with considerable population and midterm follow-up were published. De Martino et al [68] described their results with 26 (both femoral and tibial) cones at 72 months of follow-up. No evidence of loosening of the cones was detected, and the authors stated that tantalum cones for reconstruction of massive bone defects provided secure fixation and outcomes at average follow-up of 6 years.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…(19), Meneghini et al (18) and Long and Scuderi (17) having an unquestionable osteointegration of the cones and similar percent for the need of reoperation. The increase of the Knee Society score in terms of pre and postoperative numbers is similar to other studies (2,16,20).…”
Section: Discussionmentioning
confidence: 96%
“…The femoral cone augment is designed to contribute the reconstruction in rotation, and the asymmetric design follows the anatomic direction of the femoral bone during centralization. Eventual gaps between the porous surface and the host bone should be filled with morselized bone allograft, autograft or bone substitutes (3). Histological studies have shown low potential for bacterial adherence with greater leucocyte activation, reducing the risk of infections (4,5).…”
Section: Methodsmentioning
confidence: 99%
“…Among these, there was 1 RCT (level I), 13 1 cohort study (level III), 5 and 17 case series (level IV). 6,8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Thirteen studies (total 448 patients and 449 knees) 6,8,13,17,18,[20][21][22][23][24][25]27,28 and 6 studies (total 318 patients and 326 knees) 5, [14][15][16]19,26 used cone and sleeve, respectively, as an augment. Each augment was used in the tibial and femoral bone defect with all degrees of severity and with all kinds of constraint (►Table 1).…”
Section: Searchmentioning
confidence: 99%
“…Fourteen studies 5,6,[14][15][16][17]19,21,[23][24][25][26][27][28] used augment for both femur and tibia, four studies 8,13,20,29 used augment only in the tibia, and one study 18 only in the femur. Fourteen (74%) studies used augment only in AORI II and III defect and four studies included AORI type I in the evaluation.…”
Section: Surgical Interventionsmentioning
confidence: 99%